PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP NILAI PERUSAHAAN - Seto Sulaksono Adi Wibowo; Arisma Sabillilah (Ekspansi: Jurnal Ekonomi, Keuangan, Perbankan, dan Akuntansi, 2016)
Abstract: The purpose of this research is to analyze the impact of CSR reporting and every single indicator in the CSR (based on GRI indicator) on firm value (used Tobin’s Q) and which indicators are the most important concern for firm. Method that used in this research is quantitative method with panel data regression analysis. The research was conducted for mining sector and basic chemical industry sector in Indonesia Stock Exchange 2009-2013. The result of this study found that 6 indicators from CSR economy, environment, employee, HAM, sociality, and product responsibility not have an effect to firm value so it is with CSR reporting. The limitations of this research is firm didn’t publish annual report on 2009, less interest from firs to do CSR disclosure activity, and only used 2 sector industry for sample.This empirical results indicate that the stockholders didn’t put much concern into CSRD activity because it is something that firm basiclly to do. Suggest for firm that recommended to increase CSRD activity as firm’s concern to environment not only follow the rules and for next similiar research should use more sample. Keywords: Corporate Social Responsibility, Global Reporting Initiative (GRI), Firm’s Value,       Tobin’s Q